Helicobacter pylori and the Prevention of Gastric Cancer. (1st May 2004) - Sullivan, Terrence; Ashbury, Fredrick D; Fallone, Carlo A; Naja, Farah; Schabas, Richard; Hébert, Philip C; Hunt, Richard; Jones, Nicola
Abstract : BACKGROUND: Helicobacter pylori is an important cause of stomach cancer that infects a substantial proportion of the Canadian adult population. H pylori can be detected by noninvasive tests and effectively eradicated by medical treatment. Screening for and treatment of H pylori may represent a significant opportunity for preventive oncology. METHODS: Cancer Care Ontario organized a workshop held in Toronto, Ontario, on October 24 and 25, 2002, to: review the current state of knowledge regarding H pylori treatment and cancer prevention; determine if there is currently sufficient evidence to consider the promotion of H pylori treatment for the purpose of cancer prevention; identify critical areas for research; and advise Cancer Care Ontario on H pylori and cancer prevention. RESULTS: Workshop participants developed a number of recommendations for research into the relationship between H pylori and stomach cancer, including determining the prevalence of infection in different regions of Canada, the pathogenetic sequence of carcinogenesis from H pylori infection, and the implementation of a prospective observational study. INTERPRETATION: Although the rate of H pylori infection is declining in Canada and the treatment of H pylori is generally accepted to be safe, the evidence to date may not warrant the implementation of population screening for H pylori infection to prevent gastric carcinoma in average-risk populations. Rather, a demonstration project is needed to estimate prevalence, evaluate the merits of screening, measure patient compliance and physician participation, develop education materials, establish a registry for monitoring and evaluation, and develop a quality assurance framework.